A Brief Overview of HPLC–MS Analysis of Alkyl Methylphosphonic Acid Degradation Products of Nerve Agents. (17th April 2019) - B'Hymer, Clayton
Abstract: The analysis of degradation products from the classic chemical warfare nerve agents by high-performance liquid chromatography–mass spectrometry has been of much interest in recent years owing to the possible use as a terrorist weapon, and the incidents of chemical weapon usage in recent years in war torn countries. The alkyl methylphosphonic acid degradation products are of a particular interest, and they represent a specific chromatographic technical challenge for use in typical separation systems. Various published methods are summarized in this review and some of the problems associated with the analysis of these compounds are discussed. Future trends of the analysis in this area of research are also considered.